2014
DOI: 10.1590/s1806-37132014000400009
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage induced by cigarette smoke exposure in mice: impact on lung tissue and diaphragm muscle,

Abstract: OBJECTIVE: To evaluate oxidative damage (lipid oxidation, protein oxidation, thiobarbituric acid-reactive substances [TBARS], and carbonylation) and inflammation (expression of phosphorylated AMP-activated protein kinase and mammalian target of rapamycin [p-AMPK and p-mTOR, respectively]) in the lung parenchyma and diaphragm muscles of male C57BL-6 mice exposed to cigarette smoke (CS) for 7, 15, 30, 45, or 60 days. METHODS: Thirty-six male C57BL-6 mice were divided into six groups (n = 6/group): a control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 35 publications
4
11
0
5
Order By: Relevance
“…Importantly, this mouse model is a valuable tool for further examination of the role of smoking in the systemic pathogenesis in COPD, such as respiratory [62][63][64] and skeletal muscle atrophy and dysfunction. [31][32][33] In conclusion, in this report, we demonstrate the effects of chronic cigarette exposure on actionpotential induced Ca 21 transients in intercostal and intrinsic foot muscles. The intrinsic muscles of the foot are important for ambulation and balance in bipeds and quadrupeds, including humans and small mammals.…”
Section: Limitations Of the Mouse Model Of Cigarette Smokesupporting
confidence: 60%
See 3 more Smart Citations
“…Importantly, this mouse model is a valuable tool for further examination of the role of smoking in the systemic pathogenesis in COPD, such as respiratory [62][63][64] and skeletal muscle atrophy and dysfunction. [31][32][33] In conclusion, in this report, we demonstrate the effects of chronic cigarette exposure on actionpotential induced Ca 21 transients in intercostal and intrinsic foot muscles. The intrinsic muscles of the foot are important for ambulation and balance in bipeds and quadrupeds, including humans and small mammals.…”
Section: Limitations Of the Mouse Model Of Cigarette Smokesupporting
confidence: 60%
“…Nevertheless, whole‐body cigarette smoke exposure has been previously demonstrated to produce emphysematous mice, with alveolar destruction and airspace enlargement, the hallmarks of emphysema. Importantly, this mouse model is a valuable tool for further examination of the role of smoking in the systemic pathogenesis in COPD, such as respiratory and skeletal muscle atrophy and dysfunction …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 26 , 35 Carlos et al, 26 in a study in which male (C57BL/6) mice were exposed to smoke from 12 cigarettes a day for 7, 15, 30, 45, and 60 days, identified that the oxidative stress induced by cigarette smoke caused changes in the lungs and in the diaphragm. Those authors added that the oxidative stress caused by exposure to cigarette smoke occurs first in the skeletal muscle and subsequently in the lung tissue.…”
Section: Discussionmentioning
confidence: 99%